ANALISA PERBANDINGAN ANTARA TEMPERATUR DAN TEKANAN TERHADAP KANDUNGAN AIR YANG HILANG DI STRIPPER - Shahab, Aliyah (Politeknik Negeri Sriwijaya, 2017)
Stripper is a process of separation between two mixed liquid substances by using a gas phase substance as a separator. In this case glycerin and water are used as mixed substances and steam is used as a separator in order to remove the moisture present in glycerine. In the separation process used variables such as temperature and pressure as a comparison, with the aim of knowing at the temperature and pressure of how much moisture content is lost. The results obtained from this study is that if the temperature and pressure are higher then the moisture content will be more and more, ie at a temperature of 140oC and a pressure of 45 psi moisture content lost as much as 50 ml. It can be concluded that temperature and pressure are very influential in removing moisture content in glycerin, because at high temperature and pressure it will get better steam so that separation in column stripper can occur maximally.